KEMITRAAN SEKOLAH MENENGAH KEJURUAN DENGAN DUNIA USAHA DAN DUNIA INDUSTRI (Kajian aspek Penhgelolaan Pada SMK Muhammadiyah 2 Wuryantoro Kabupaten Wonogiri) - Ixtiarto, Bambang (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2016)
The purposes of this study in SMK Muhammadiyah 2 Wuryantoro are 1) to describe the partnerships management planning with business and industrial world, 2) to describe the implementation of partnerships with business and industrial world, and 3) to describe the control implementation partnerships with business and industrial world.The research is a qualitative descriptive research with the ethnographic research design. The tecnique of data collected Â in this research is using field research. Data analysis used is an interactive analysis.The results of this study are the partnerships management planning in SMK Muhammadiyah 2 Wuryantoro done to manage potential schools in favor of cooperation with business and industrial world: a) Planning school promotion in establishing communication with business and industrial world, in the synchronization of the curriculum, prakerin students, graduate placement, teacherâ€™s on the job training place, b) Utilize the specific role of the business and industrial world a sa guest teacher, school funding, and scholarships, c) The business and industrial world cooperation outlined in the form of the MoU. The implementation of cooperation created MoU, the contents for the agreed areas of cooperation including validation and synchronization curriculum, industry visits, guests teacher, industry work practices, a vocational competency test (UKK), teacher on OJT ,certification, and recrutment/placement of graduates.